Developing Business Plan For YouTube Gaming (Journal of Business and Management, 2022)
This documents dives deep into the opportunity to create a business plan for YouTube gaming in Indonesia. It may serve as a stepping stone for the standardization of the YouTube Gaming business plan provides information about requirements and workflow business process for those starting as Gaming YouTubers. From this document a plan is made for the channel to reach monetization in a year of how many videos should be made and the duration of each videos. An investment of around Rp30,000,000 to build the hardware needed to start the channel, and may cost less if user already have base hardware to start with. Once the channel get its monetization, the revenue from the channel could go to around $1,000 excluding external revenue from websites outside of YouTube such as Patreon.